2023
DOI: 10.3390/v15010148
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of Insecticide Resistance Mutations and Pathogen Circulation in Sand Flies from Emilia-Romagna, a Leishmaniasis Endemic Region of Northern Italy

Abstract: The continuously expanding distribution of sand flies, proven vectors of Leishmania and of several phleboviruses, is a growing public health issue in Europe. Especially in Italy, visceral leishmaniasis (VL) is occurring with increasing incidence northward, in previously non-endemic provinces. Around the globe, disease elimination efforts largely focus on sand fly vector insecticidal control, often leading to the development of resistance. In Emilia-Romagna (ER), northern Italy, insecticides are heavily applied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…This, in turn, prompted the government to implement a sand fly control program, ultimately resulting in a decrease in case rates [42]. This was the situation in our research, where CL cases gradually declined to 33 cases in 2009, then fluctuated with increases and decreases, justifiable to some extent by the excessive use of insecticides in the health sector as well as on farms, which contributed to the development of insecticide resistance in the disease vectors [43]. Additionally, inadequate sanitation and irregular household garbage disposal, combined with the construction of rural houses from mud with wall cracks, facilitate the breeding of phlebotomine sand flies [44,45].…”
Section: Discussionmentioning
confidence: 67%
“…This, in turn, prompted the government to implement a sand fly control program, ultimately resulting in a decrease in case rates [42]. This was the situation in our research, where CL cases gradually declined to 33 cases in 2009, then fluctuated with increases and decreases, justifiable to some extent by the excessive use of insecticides in the health sector as well as on farms, which contributed to the development of insecticide resistance in the disease vectors [43]. Additionally, inadequate sanitation and irregular household garbage disposal, combined with the construction of rural houses from mud with wall cracks, facilitate the breeding of phlebotomine sand flies [44,45].…”
Section: Discussionmentioning
confidence: 67%
“…Mosquito species were molecularly identified as previously described [ 28 , 29 ]. Briefly, members of Cx.…”
Section: Methodsmentioning
confidence: 99%
“…Anopheles mosquitoes were molecularly differentiated by partial amplification of the ITS2 and mitochondrial cytochrome c oxidase I gene (COI) [ 32 , 33 ]. Sand fly species discrimination was performed based on the COI genomic fragment, as previously described [ 29 , 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…Recent monitoring studies have suggested that kdr mutations are typically absent from Phlebotomus species in Greece and Italy (Balaska et al, 2023). Nonetheless, the kdr (L995F and L995S) mutations have been recorded in Ph.…”
Section: Voltage Gated Sodium Channel (Vgsc) Orthologsmentioning
confidence: 99%